Complete androgen insensitivity syndrome with a large gonadal serous papillary cystadenofibroma - Ozhan Ozdemir; Mustafa Erkan Sari; Evren Akmut; Vafa Selimova; Tugba Unal; Cemal Resat Atalay (Journal of Human Reproductive Sciences, 2014)
We present a patient with complete androgen insensitivity syndrome (CAIS) diagnosed with a serous papillary cystadenofibroma. A 41-year-old married female with a mass in the left inguinal region and a history of primary amenorrhea. A bulging mass of 13.7 cm × 8 cm × 12.4 cm in the left inguinal region extending from the hip joint to the level of labia majus, and a 3.2 cm × 2.8 cm mass in her right inguinal region were found by ultrasonography and magnetic resonance imaging. We performed bilateral gonadectomy. The pathology showed testicular tissue in the right inguinal mass and a serous papillary cystadenofibroma in the left one. CAIS is an infrequent clinical entity, occurrence of serous papillary cystadenofibroma is even rarer in this syndrome serous cystadenofibroma should come to mind in patients with a huge inguinal mass. Gonadectomy should be performed right after puberty to prevent the risk of malignancy development in the testes.